Histomorphometric study of seminiferous tubules and epididymis in adult ram - Ali A. Tala’a; Hamdi , Y.D (University of Thi-Qar Journal of agricultural research, 2023)
This research set out to examine the epididymis and seminiferous tubules of adult male Rams, use both histological and histomorphometric methods. For this purpose, ten paired of testis of healthy adult local rams were taken from local abattoir in Fallujah. Tissue was removed and cut into tiny pieces from different parts of the testicles before being put in Bouin’s solution. The tissue samples were processed by common paraffin technique then stained with routine H & E stain as well as Masson’s trichrome stain. According to the results of the present histological analysis, the ram’s testis is enclosed by a capsule of thick irregular connective tissue, and its lobules are separated by trabecular and interlobular septa, with seminiferous tubules and interstitial tissue making up each lobule. Spermatogenic cells and Sertoli cells border the seminiferous tubules. Spermatozoa develop from spermatogenic cells. Spermatogonia are the earliest stages of spermatogenic cells; they are tiny, spherical cells with black, spherical nuclei that sit on the basement membrane. Primary spermatocytes, which are bigger cells with often-distinct chromatin, are generated during mitosis in the spermotogonia. Because of their rapid second meiotic division and subsequent formation of haploid spermatids, secondary spermatocytes are seldom seen. Clustered near the seminiferous tubule’s lumen, the spermatids are spherical cells with pale nuclei. There are less Sertoli cells (sustentacular cells) than spermatogenic cells. The nucleus is oval or triangular in shape and pale in colour, with a large nucleolus. Leydig cells are found in the connective tissue between neighbouring tubules. Epithelium that is pseudostratified lines the epididymis. The stereocilia are long cytoplasmic structures that extend into the lumen. Circular smooth muscle is present in varying amounts, and the epithelium is supported by a connective tissue lamina propria.In conclusion, the current study concluded that the thickness of the epithelium of epididymis was decrease toward the tail while the thickness of the smooth muscle layer was increase toward the tail.